PENGARUH MACAM MEDIA TANAM DAN PENAMBAHAN NUTRISI TERHADAP PERTUMBUHAN DAN HASIL JAMUR TIRAM (Pleurotus ostreatus L.) - Maria Margaretha Lolonlun; Maria Theresia Darini; Djoko Heru Pamungkas (Universitas Sarjanawiyata Tamansiswa, 2017)
This study on the effect of the addition of coconut water and sugar water in a variety of growing media on growth and yield of white oyster mushroom (Pleurotus ostreatus) has been carried out at home Current Mushrooms, Jln. Merapi Golf West, Gambretan village, Umbulharjo village, Cangkringan sub-district, Sleman, Yogyakarta. The purpose of research is to study the potential powder salaried and rice husk as alternative growth medium oyster mushroom, studied the effects of a dose of coconut water and sugar water to the increased productivity of oyster mushrooms, and studying the interaction between the kinds of media and dosage of coconut water and sugar water on growth and yield mushrooms oyster. This research is compiled in a completely randomized design (CRD) factorial, with three replications. The first factor is the material planting medium consists of two levels of media sebuk saws (S1) of 100 kg and media rice husk (S2) of 100 kg and factors that both doses of coconut water and sugar water consists of five levels, control (without the administration of coconut water and water sugar) M0, coconut water 50 ml / baglog (M1), sugar water 50 ml / baglog (M2), coconut water is 100 ml / baglog (M3), sugar water 100 ml / baglog (M4). Variables included age observations grow mycelium, grows fruit bodies age, the number of mushroom fruit body in a clump, fresh weight of fruit weight, fruit body diameter, stem length, ferkuensi harvest, harvest interval and endurance fruit. There is interaction between types of media and the addition of nutrients to the growing mycelium variebel age, the age of the fruit body grows, the number of fruit bodies, fresh weight, diameter badan buah, stem length, interval and frequency of interaction does not occur. Wide media sawdust and rice husk as alternative growing media gave different results for the growth and production of oyster mushrooms. Each treatment nutrients to the medium that provides the most influence both the growth and production of oyster mushrooms is sawdust 100kg, rice husks 100kg produce mycelium growth full, harvest interval, body diameter of fruit, average fresh weight/baglog 426.70 g, and successive harvest interval is 14.67 days